2019
DOI: 10.4236/ce.2019.1012229
|View full text |Cite
|
Sign up to set email alerts
|

Creative Problem-Solving (CPS) Skills among University Students

Abstract: Malaysia had launched the National Education Blueprint (Higher Education) 2015-2025 aimed to improve higher education. There are six learner's aspirations that have been identified to promote excellence in higher education. The blueprint aimed to develop the attributes of students and graduates in line with the world of 21 st century education. One of the attributes that have been emphasized is Creative Problem-Solving (CPS) skills. CPS skills refer to the ability of individuals to solve problems through the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…These results are consistent with a study by Kumnuansin et al (2020), who reported that there was a need to develop the ability to solve problems in new ways among undergraduate students in Thailand. They also concur with the findings of Amran et al (2019), who showed that creative problem-solving is one of the significant deficiencies in the 21 st century among Malaysian undergraduate students, which possibly results from the fact that university students are accustomed to listening to lectures and taking in knowledge without challenge, and they are thus too afraid or embarrassed to express their thoughts. Eubanks et al (2010), however, found that most university students in the United States also lacked the capacity to establish a connection with a problem and generate new solutions, so this may not be a culturally specific issue in undergraduates and is worthy of further exploration.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These results are consistent with a study by Kumnuansin et al (2020), who reported that there was a need to develop the ability to solve problems in new ways among undergraduate students in Thailand. They also concur with the findings of Amran et al (2019), who showed that creative problem-solving is one of the significant deficiencies in the 21 st century among Malaysian undergraduate students, which possibly results from the fact that university students are accustomed to listening to lectures and taking in knowledge without challenge, and they are thus too afraid or embarrassed to express their thoughts. Eubanks et al (2010), however, found that most university students in the United States also lacked the capacity to establish a connection with a problem and generate new solutions, so this may not be a culturally specific issue in undergraduates and is worthy of further exploration.…”
Section: Discussionsupporting
confidence: 87%
“…(2020) , who reported that there was a need to develop the ability to solve problems in new ways among undergraduate students in Thailand. They also concur with the findings of Amran et al. (2019) , who showed that creative problem-solving is one of the significant deficiencies in the 21 st century among Malaysian undergraduate students, which possibly results from the fact that university students are accustomed to listening to lectures and taking in knowledge without challenge, and they are thus too afraid or embarrassed to express their thoughts.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The ability of students to produce new solutions in resolving algebra problems involving money operations is the impact of involving the context of everyday problems. This is relevant with the results of studies [31], [32], [33], [34]. The ability of students to produce new solutions in designing a flat shape that has specific characteristics is the impact of involving students in the learning carried out by the teacher.…”
Section: Discussionmentioning
confidence: 95%
“…The concept of Creative Problem Solving (CPS) is not a new skill, but it does take into account the role of creativity in solving a problem. This is proven true as there is a link between human thinking and the context of life in which knowledge and skills in solving a problem can be developed and channelled through the application of daily life (Amran et al, 2019).…”
mentioning
confidence: 99%